Being an English academic: a social domains account. (3rd September 2018) - Sealey, Alison
ABSTRACT: This paper considers the differential placements of social actors in the contemporary English university, as practices consistent with neoliberal ideologies become increasingly influential. It uses Layder's theory of 'social domains' and the first-hand experiences of the author to explore how the options available – to students, those on precarious conditions of employment, and those occupying more influential roles in the institution – change in relation to alterations in structured social relations. Examples are provided of interventions by people opposed to both the rhetoric and the reality of developments in the sector, and reasons for their limited effectiveness are also discussed.